Predictive Models in Differentiating Vertebral Lesions Using Multiparametric MRI - Rathore, R.; Parihar, A.; Dwivedi, D.K.; Dwivedi, A.K.; Kohli, N.; Garg, R.K.; Chandra, A. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Conventional MR imaging has high sensitivity but limited specificity in differentiating various vertebral lesions. We aimed to assess the ability of multiparametric MR imaging in differentiating spinal vertebral lesions and to develop statistical models for predicting the probability of malignant vertebral lesions.MATERIALS AND METHODS: One hundred twenty-six consecutive patients underwent multiparametric MRI (conventional MR imaging, diffusion-weighted MR imaging, and in-phase/opposed-phase imaging) for vertebral lesions. Vertebral lesions were divided into 3 subgroups: infectious, noninfectious benign, and malignant. The cutoffs for apparent diffusion coefficient (expressed as 10−3 mm2/s) and signal intensity ratio values were calculated, and 3 predictive models were established for differentiating these subgroups.RESULTS: Of the lesions of the 126 patients, 62 were infectious, 22 were noninfectious benign, and 42 were malignant. The mean ADC was 1.23 ± 0.16 for infectious, 1.41 ± 0.31 for noninfectious benign, and 1.01 ± 0.22 mm2/s for malignant lesions. The mean signal intensity ratio was 0.80 ± 0.13 for infectious, 0.75 ± 0.19 for noninfectious benign, and 0.98 ± 0.11 for the malignant group. The combination of ADC and signal intensity ratio showed strong discriminatory ability to differentiate lesion type. We found an area under the curve of 0.92 for the predictive model in differentiating infectious from malignant lesions and an area under the curve of 0.91 for the predictive model in differentiating noninfectious benign from malignant lesions. On the basis of the mean ADC and signal intensity ratio, we established automated statistical models that would be helpful in differentiating vertebral lesions.CONCLUSIONS: Our study shows that multiparametric MRI differentiates various vertebral lesions, and we established prediction models for the same.AUCarea under the curveFNAfine-needle aspirationGPIinfectiousGPNnoninfectious benignGPMmalignantmpMRImultiparametric MRISEsensitivitySIRsignal intensity ratioSpspecificity